The role of cytology as an effective tool in management of omental and peritoneal lesions: Experience of a large health care system. Issue 2 (6th December 2021) - Kataria, Nidhi; Hacking, Sean; Abdelwahed, Mohammed; Burke, Alexander; Karam, Priyanka; Gimenez, Cecilia; Das, Kasturi; Khutti, Seema
Abstract: Background: The aim of this study is to assess the efficacy of cytology in omental or peritoneal lesions. Methods: A retrospective review of the pathology database for cytology cases of peritoneal or omental nodules over a 3‐year period (2016–2018) was conducted. The cases consisted of either FNA only (FO); FNA and Core biopsy (FCB) or Touch prep and core biopsy (TCB). Cases were further divided based on the prior history of carcinoma. Concordance rates of cytologic diagnosis with histologic diagnosis were studied. Results: Out of 104 cytology cases reviewed, 60 (57.7%) had prior history of cancer (PHC) and 44 (42.3%) had no prior history of cancer (NPHC). Of the cases with PHC, 43(71.66%) were recurrence, 10 (16.66%) were second cancer, and 7 (11.66%) were non‐neoplastic lesions. Of the cases with NPHC, 38 (86.4%) had a second cancer diagnosis, while 6 (13.6%) were non‐neoplastic. For FO only cases, 11 of 35 (31.4%) had follow up and 9 of 11 (81.8%) were concordant. For FCB cases, 6 out of 39 (15.4%) had follow up and 6 (100%) were concordant. For TCB cases, 9 out of 30 (30%) had follow up and 9 (100%) were concordant. A definite diagnosis was reached in 30/35, 39/39, and 29/30 cases in FO, FCB, and TCB, respectively. Conclusion: In summary, cytologic evaluation of omental lesions is an effective tool in providing accurate diagnosis and guiding further management. Also, the results based on our study show that the combined techniques are superior at reaching a definitive diagnosis.